2018
DOI: 10.1016/j.ajpath.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Drives Neutrophil-Mediated Pulmonary Inflammation Associated with Bacteremia in Murine Models of Colitis

Abstract: Inflammatory bowel disease (IBD) is associated with several immune-mediated extraintestinal manifestations. More than half of all IBD patients have some form of respiratory pathology, most commonly neutrophil-mediated diseases, such as bronchiectasis and chronic bronchitis. Using murine models of colitis, we aimed to identify the immune mechanisms driving pulmonary manifestations of IBD. We found increased neutrophil numbers in lung tissue associated with the pulmonary vasculature in both trinitrobenzenesulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 67 publications
(55 reference statements)
7
40
0
Order By: Relevance
“…2 This loss of epithelial integrity promotes bacteraemia in IBD patients [3][4][5] and these pathologies are apparent in animal models of colitis. 6,7 In IBD patients, bacteraemia can promote extra-intestinal inflammation and approximately half of IBD patients have secondary organ pathologies that contribute significantly to disease morbidity. 8 An increasing number of studies suggest that abnormal lung pathology is a common feature of IBD, 9,10 with subclinical disease observed in over one third of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 This loss of epithelial integrity promotes bacteraemia in IBD patients [3][4][5] and these pathologies are apparent in animal models of colitis. 6,7 In IBD patients, bacteraemia can promote extra-intestinal inflammation and approximately half of IBD patients have secondary organ pathologies that contribute significantly to disease morbidity. 8 An increasing number of studies suggest that abnormal lung pathology is a common feature of IBD, 9,10 with subclinical disease observed in over one third of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…11 While some therapies can promote lung damage, 12 in the majority of cases pulmonary disease associated with IBD is idiopathic, and animal studies have demonstrated that lung pathologies similar to those observed in IBD patients are evident in animal models of colitis. 7,13,14 Our recent studies suggest that pulmonary manifestations of colitis arise from neutrophilia associated with loss of intestinal epithelial integrity and subsequent bacteraemia. 7 An increased bacterial load in the lungs may be the initiating factor for the observed pulmonary neutrophilia, although the pathway initiating this response is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The airway/lung microbiota is emerging as a contributor and may be majorly altered in COPD with high biomass and less diversity compared to the healthy state . Gut microbiota and pathology may also contribute through systemic inflammation . The most commonly identified bacterial ‘colonizers’ are non‐typeable Haemophilus influenzae (NTHi, ~60%), Moraxella catarrhalis (~48%) and Streptococcus pneumoniae (~28%) .…”
Section: Bacterial Colonization and Infection In Copdmentioning
confidence: 99%
“…22,23,30,31 Gut microbiota and pathology may also contribute through systemic inflammation. 21,31,32 The most commonly identified bacterial 'colonizers' are non-typeable Haemophilus influenzae (NTHi,~60%), Moraxella catarrhalis (~48%) and Streptococcus pneumoniae (~28%). 28,33 Respiratory bacterial colonization in COPD is considered to be dynamic, as it frequently changes in terms of both strains and species, but predominantly with these same bacteria.…”
Section: Bacterial Persistencementioning
confidence: 99%